(untitled) (Research, Society and Development, 2021)
Diabetes is a metabolic disorder with a high prevalence throughout the world population and high morbidity due to its complications in the cardiovascular and neurological systems. Among the complications most evident in the clinical routine are the wounds, insidious and difficult to heal, that evolves to the amputation, initially of a polydactyl, and may even progress to the hip joint disarticulation. It is widespread among the world that the properties of certain natural products for the treatment of wounds, in different presentations, by the action of its bioactive compounds. The aim of this study was to analyze the profile of patients and to know the natural products that are being used in the treatment of diabetic foot syndrome. This is a cross-sectional cohort study, through an interview with patients with diabetic foot ulcers, with questions about the social and demographic aspects, treatment and symptomatic evolution. For statistical analysis, the Excel® and BioEstat 5.0® programs were used. It was observed a change in the profile of these patients compared to previous studies, showing an increase in prevalence in a population with higher level of education and also was observed the prevalence in the female sex, corroborating with other studies. In addition, it was found that most of them had been diagnosed at least 10 years ago and that most of them are service and commerce workers. It is understood the need to create a multidisciplinary healthcare team to control diabetes and early identification of diabetic foot, as well as the need for training of teams in specialized care.